ANALISIS YURIDIS KEWENANGAN PENYELESAIAN SENGKETA PEMBIAYAAN KONSUMEN DI INDONESIA - Wibowo, Afrizal Mukti; Sukarmi, Sukarmi; Hamidah, Siti (Legality : Jurnal Ilmiah Hukum, 2019)
Consumer financing disputes can be resolved by litigation and non-litigation. However, the choice of dispute resolution raises an competence dispute between dispute resolution institutions. Thus giving rise to legal uncertainty and losses for the parties to the dispute. The purpose of this study is to analyze the competence of consumer financing dispute resolution institutions in Indonesia. This research is a normative juridical approach with a legal, conceptual and case approach. The results of this study are that each dispute resolution institution has the attribute attributive in resolving consumer financing disputes. The competence to settle consumer financing disputes for each settlement institution must pay attention to two aspects, including the types of consumer financing disputes; and the choice of dispute resolution based on the agreement of the parties.